Variance Analysis of Photoplethysmography for Blood Pressure Measurement - Hendrana Tjahjadi; Kalamullah Ramli (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
The emergence of photoplethysmography for blood pressure estimation is offering a more convenient method. The elements of photoplethysmography waveform is crucial for blood pressure measurement. Several photoplethysmography elements are still not completely understood. The purpose of this study was to investigated corelation of photoplethysmography elements with blood pressure using statistical approach. Analysis of variance test (ANOVA) was conducted to see if there are any correlation between elements of photoplethysmography with blood pressure. This study used 10 volunteers without an ethical clearance. Photoplethysmography waveform and blood pressure measurements were taken through the patient monitor equipment DatascopeTM. As the result, value factor from the arithmetic is 35.67 and value factor from the table is 3.14. The value of F arithmetic (35.67) > F table (3.14). The correlation of diastolic time (Td) is negative with systolic arterial pressure (SAP) and the correlation of systolic amplitude (As) is positive with diastolic arterial pressure (DAP). The results showed elements of photoplethysmography can be used to estimation blood pressure. The emergence of photoplethysmography for blood pressure estimation is offering a more convenient method. The elements of photoplethysmography waveform is crucial for blood pressure measurement. Several photoplethysmography elements are still not completely understood. The purpose of this study was to investigated corelation of photoplethysmography elements with blood pressure using statistical approach. Analysis of variance test (ANOVA) was conducted to see if there are any correlation between elements of photoplethysmography with blood pressure. This study used 10 volunteers without an ethical clearance. Photoplethysmography waveform and blood pressure measurements were taken through the patient monitor equipment DatascopeTM. As the result, value factor from the arithmetic is 35.67 and value factor from the table is 3.14. The value of F arithmetic (35.67) > F table (3.14). The correlation of diastolic time (Td) is negative with systolic arterial pressure (SAP) and the correlation of systolic amplitude (As) is positive with diastolic arterial pressure (DAP). The results showed elements of photoplethysmography can be used to estimation blood pressure.